Pengaruh Pemasaran Digital dan Kualitas Produk terhadap Keputusan Pembelian Kosmetik Merek Wardah di Toko Alisa Simpang Mangga Rantauprapat - Harahap, Alia Wardah Fadilah; Sukmal, Jeni; Rambe, Shopiah Anggraini (IAI Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine the influence of digital marketing and product quality, digital marketing and product image on purchasing decisions for Wardah brand cosmetics at the Alisa Simpang Mangga Rantau store. This research aims to determine and analyze the influence of product quality and digital marketing on Wardah brand loyalty. This research uses a quantitative approach with descriptive methods. Quantitative descriptive is a type of research to carry out data analysis by providing a description or explanation of the data that has been collected. The instrument in this research used a questionnaire and for sampling used the Lemeshow theory approach. Data analysis techniques in this research use validity tests, reliability tests, normality tests, heteroscedasticity tests, multicollinearity tests, coefficient of determination tests, hypothesis tests, partial tests, simultaneous tests, and the method used is the multiple linear regression analysis method. The results of this research show that Product Quality has a positive and significant influence on Brand Loyalty and Digital Marketing has a positive and significant influence on Brand Loyalty.